Regional Development in the Philippines: A Review of Experience, State of the Art and Agenda for Research and Action - Ruben G. Mercado (Philippine Institute for Development Studies (PIDS), 2002)
Regional development policy and practice took significant transformations over the last five decades. Its relevance has been challenged in recent years by the new economic geography that emerged in view of globalization and as most nations veer towards a more democratic and decentralized approach to plan and implement their various development activities. Given these advances, the emergence of new regional dynamics calls on countries to fine-tune current regional development perspectives and/or to develop new ones that are not only more in sync with the present and future global context and with the governance systems being adopted that are becoming more and more decentralized and grassroots oriented. The Philippines is one of the developing countries that have made great strides in adopting regional development perspectives in national development planning. As early as the mid-70s, serious efforts have been taken to put regional planning in the mainstream of national development activities. After about thirty years of regional planning, it is an opportune time to reexamine the countrys experience thus far and reflect on how the current policy and practice can be reconfigured to suit present and likely future development concerns. This study is an attempt to put together these long years of experience through a reexamination of the original ideas and concepts of regional development and reflecting on how the same have influenced the perspectives of the countrys policymakers in actual regional policy and planning. The objectives of this study also align with the current realization that there is a need to provide a stronger research base that will aid in the more meaningful integration of regional concerns in national development policy analysis and formulation. It is hoped that this attempt at providing a comprehensive assessment of regional development theories and practices and suggesting a research agenda will help jumpstart more studies that will fill such gap.
Keywords: 330; globalization; development program; research; decentralization; Regionalökonomik; Regionalpolitik; Regionalentwicklung; Entwicklungstheorie; Theorie; Philippinen